IDENTIFIKASI PERMASALAHAN BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS PASIR PENGARAIAN - -, Hardianto (Edu Research, 2014)
The problem of the research are most students seldom read book , thestudents are passive in the class and they are not preparing the subject before class is begun. The purpose of the research are to know the way/strategy of biology students’ learning, to know the factors of students’ learning difficulties and to know the learning problem solving. This research is descriptive qualitative. The informan of research is biology’s students. Sample was taken by convenience sampling. Technique collecting data was done by observation, documentation and interview. Authenticity of data was done by trianggulation and analyzing data was done by analyzing all data, reducing data, presenting data, making data verification and conclusion